Anesthetic Approach and Decreased Need for Anesthetic Agents in a Patient Suffering From Pantothenate Kinase Associated Neurodegeneration (Hallervorden-Spatz) - Yorulmaz, İlknur Suidiye and Ersoy Karka, Özlem and Usta, Ömer Batuhan (Cerrahpaşa Medical Journal, 2020)
We present our anesthetic approach to a patient with Pantotenat Kinase Associated Neurodegeneration (PKAN) (formerly called Hallervorden-Spatz disease) who underwent thyroidectomy under general anesthesia. A 46-year-old female patient was admitted to the general surgery department because of dysphagia and swallowing sensation. The patient was dystonic, aphonic, and she was only able to communicate with eye movements. High cortical functions were normal. The patient was operated under general anesthesia. Thiopental, rocuronium, and fentanyl were used for induction and no intubation difficulty was observed. Anesthesia was maintained with sevoflurane and fentanyl under Bispectral Index (BIS) monitoring. It was observed that the need for anesthetic agents decreased, so BIS levels of 38%-40% were obtained with inhalation of 0.6 minimum alveolar concentration sevoflurane. In the postoperative period after extubation using sugammadex, the patient was transferred to the intensive care unit. PKAN is an autosomal recessive syndrome characterized by dystonia, Parkinson disease-like symptoms, and iron deposition in the brain, which is caused by panthotenate kinase 2 enzyme mutation. The anesthetic approach is characterized by reduced mouth opening, atetoid posture, dystonic movements, and cervical pathologies. In our case, endotracheal intubation was easy and the need for anesthetic agents was considerably reduced. Our absolute recommendation is to involve neuromonitoring techniques in the anesthetic management of neurodegenerative diseases. Cite this article as: Yorulmaz İS, Ersoy Karka Ö, Usta ÖB. Anesthetic Approach and Decreased Need for Anesthetic Agents in a Patient Suffering From Pantothenate Kinase Associated Neurodegeneration (Hallervorden-Spatz). Cerrahpaşa Medical Journal 2020; 44(2): 108-111.